Sphere Mapping: A Method for Responsive Surface Rationalization. (September 2013) - Beorkrem, Chris; McGregor, Mitchell; Polyakov, Igor; Desimini, Nicole
The method proposed in this project addresses the parametric manipulation of a given pattern to respond directly to a parametric surface. The research attempts to propose a method for attaching fixed sized objects to a free flowing surface or "blanket." The model can be used to interrogate a series of shapes and forms with the same componentry. Continuing the research of Kevin Rotheroe, Yale University and founder of FreeForm Design. Rotheroe and his students developed a series of studies in material and surface properties. By utilizing a proven pattern, the proposed method sets parameters derived from the formal properties of the original pattern and produces a new pattern that is responsive to the curvature of a complex surface. The workflow developed in this research consists of a complex blending of tools in Rhino Grasshopper and Gehry Technologies Digital Project . The intent is to achieve the aesthetics and structure offered by Rotheroe's original research and to add a responsive precision that provides an accurate adaptation of the pattern based on curvature of a specific computationally defined surface.